Anticipating the apocalypse: Monstrous educational futures. (October 2019) - Priyadharshini, Esther
Highlights: The telos of education tied to 'the real' confines notions of futures which the speculative and the fantastic can open up. To young people in the study futures are unfathomable, but anxieties relate to continuing monstrosities of the present. Apocalyptic imaginings critique older systems and exhibit an infectious thrill in planning to survive inhospitable futures. Including the monstrous can strengthen creative responses to emerging challenges and attend to a range of desires and fears. It is worth experimenting with affective, speculative and anticipatory methods to move education and research in new directions. Abstract: Educators have been called to engage with the ontological problematic of the 'future' – its not-knowable nature – and to consider the radical implications of this notion for education. However, orthodoxies of schooling, research and institutional logics can work to constrain the space and tone of futures talk. One way of expanding the scope of such talk is to engage with the radical potentialities of futures by making space for youth preoccupations and speculations that exceed realist notions of how to anticipate futures and prepare for them. This paper explores how functions of the 'speculative' and 'monstrous', as elaborated in literary and popular culture analysis find echoes in data gathered with youth about their visions of 'fantastic' futures. These fantastic/monstrous narratives reveal the salience of dystopian/apocalyptic visions for youth and the different functions they can fulfil. These encounters also expose challenges for education and research that must be met if they are to remain relevant to young peoples' needs to imagine, anticipate and prepare for monstrous futures.